Template induced structural isomerism and enhancement of porosity in manganese(II) based metal-organic frameworks (Mn-MOFs) - Panda, Tamas; Pachfule, Pradip; Banerjee, Rahul (Chemical Communications, 2011)
Three new metal-organic framework isomers have been synthesized by using the organic linker 5-triazole isophthalic acid and Mn(NO3)(2)center dot xH(2)O. Structural conversions from non-porous to porous MOFs due to the template effect have been observed. The cross-sectional pore apertures of the resulting Mn-MOFs are comparable to the molecular dimensions of the template (pyrazine and 4,40-bipyridine). The periodic increased porosity in Mn-MOFs depending on the size of the template used has been further confirmed by the CO2 adsorption isotherms.

Transition-metal-free multicomponent reactions involving arynes, N-heterocycles, and isatins - Bhunia, Anup; Roy, Tony; Pachfule, Pradip; Rajamohanan, Pattuparambil R.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2013)
Mix and match: With isoquinoline as the nucleophilic trigger, multicomponent reactions afforded spirooxazino isoquinoline derivatives, proceeding through 1,4-dipolar intermediates. The use of pyridine as a nucleophile furnished indolin-2-one derivatives, with the reaction likely proceeding through a pyridylidene intermediate.